Non-Coding RNAs: Strategy for Viruses’ Offensive - Gallo, Alessia (Noncoding RNA, 2020)
The awareness of viruses as a constant threat for human public health is a matter of fact and in this resides the need of understanding the mechanisms they use to trick the host. Viral non-coding RNAs are gaining much value and interest for the potential impact played in host gene regulation, acting as fine tuners of host cellular defense mechanisms. The implicit importance of v-ncRNAs resides first in the limited genomes size of viruses carrying only strictly necessary genomic sequences. The other crucial and appealing characteristic of v-ncRNAs is the non-immunogenicity, making them the perfect expedient to be used in the never-ending virus-host war. In this review, we wish to examine how DNA and RNA viruses have evolved a common strategy and which the crucial host pathways are targeted through v-ncRNAs in order to grant and facilitate their life cycle.